2013
DOI: 10.1177/0148607112473340
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Handheld Indirect Calorimeter Against a Standard Calorimeter in Obese and Nonobese Adults

Abstract: Measurements of resting metabolic rate by the handheld indirect calorimeter tested in this study are not equivalent to measurements by standard indirect calorimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
8
0
3
Order By: Relevance
“…Anteriormente, cinco estudios habían reportado esta tendencia de medir un valor mayor en el consumo de oxígeno y del GER al compararlo con la CI estándar. (7,2,(28)(29)(30) Por el contrario, dos encontraron que MedGem subestima el valor estándar (31, 32) y cinco que la medición es equivalente a Deltatrac (28,(33)(34)(35).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Anteriormente, cinco estudios habían reportado esta tendencia de medir un valor mayor en el consumo de oxígeno y del GER al compararlo con la CI estándar. (7,2,(28)(29)(30) Por el contrario, dos encontraron que MedGem subestima el valor estándar (31, 32) y cinco que la medición es equivalente a Deltatrac (28,(33)(34)(35).…”
Section: Discussionunclassified
“…Se siguieron las instrucciones del fabricante, que indica que tras un ayuno de 12 horas, no se requiere de la estandarización previa de alimentos ni el descarte de los primeros minutos de la prueba. Las validaciones de este equipo portátil frente a la CI fueron realizadas siguiendo estas mismas condiciones (7,12).…”
Section: Materials Y Métodosunclassified
See 1 more Smart Citation
“…The VO2000 facemask (Medgraphics) was the only machine accepted based on measures coming within 5 % of those on the Deltatrac ( 12 ) . The majority of comparison studies tend to use the MedGem RMR ® , a portable calorimeter that uses a mouthpiece to measure VO 2 ; however, they report mixed conclusions ( 17 ) . Frankenfield & Coleman ( 17 ) reported that of eight portable calorimeter studies only two studies reported agreement to the Deltatrac, both reporting that this was based on there being low, non-significant differences between the machines ( 18 , 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Many 2,12,21,22 state that the handheld device is valid in both adults and children, while other studies suggest that it is not valid. [23][24][25] Other portable indirect calorimeters are not handheld and use technology that is similar to the traditional indirect calorimeter (ie, mixing chamber). 15,26 This "hybrid" technology of using a mixing chamber during gas analysis within portable indirect calorimetry may provide an advantage to the handheld device.…”
mentioning
confidence: 99%